Latest biotechnology tools and targets for improving abiotic stress tolerance in protein legumes - Détain, Alexandre; Bhowmik, Pankaj; Leborgne-Castel, Nathalie; Ochatt, Sergio (Environmental and experimental botany, 2022)
Protein legumes are among the most important crops for sustainable agriculture and global food security for decades to come. Unfortunately, they are subject to several abiotic stresses that severely limit their productivity, and this phenomenon is increasing with climate change. New Plant Breeding Technologies (NPBTs) offer novel alternatives to improve the plant performance of crops against such environmental constraints. However, the recalcitrance to transgenesis and in vitro regeneration has delayed such advances for protein legumes. This article reviews recent advances in legume crop biotechnological approaches to improve their tolerance to abiotic stresses including drought, high salinity, heat and cold, and heavy metal stress. In addition to these improvements, obtained mainly through transgenesis, we surveyed the application of tools such as CRISPR/Cas and RNA interference in legumes in a context of abiotic stress tolerance, and suggested a path to follow for gene control by these tools in legume plants, organs, or cells. Furthermore, we also discussed promising molecular targets, perspectives, and the way ahead for enhancing abiotic stress tolerance. •NPBT gave new protein legume genotypes to better cope with changing global climate.•Tolerance to drought, salinity, extreme temperatures and heavy metals were improved.•We surveyed recent advances in transgenesis, RNAi and genome editing technology.•Candidate genes modulating protein legume responses to abiotic stress are evoked.•A comprehensive survey of biotechnology-induced abiotic stress tolerance in legumes.